Improving Indonesian Learning Outcomes in Reading Comprehension Skills with the Inquiry Learning Model in Grade 4 Elementary School, Al Muhajirien Jakapermai - Nuryani Nuryani; Nidya Chandra Muji Utami; Fahrurrozi Fahrurrozi (Jurnal Syntax Admiration, 2023)
This study started from the problem of low learning outcomes of Indonesian students in Grade 4, MI Al Muhajirien Jakapermai, which only reached 61.65 and KKM only 37%. Because of this, class action research (PTK) was done in two cycles using the inquiry learning model. To make sure the learning model is used, test questions and observation sheets are used to collect data. The results showed that the use of the inquiry-based learning model could improve learning outcomes and student achievement in the second cycle. The percentage of the increase in learning outcomes from initial conditions to cycle L is 6.8%, and from cycle I to cycle Il, it is 20.0%. From the first condition to cyclase I, MOH achievement went up by 42%, and from cyclase I to cyclase II, it went up by 118.9%. Based on these results, it is suggested that 4th graders at SD Jakapermai use the inquiry learning model to learn Indonesian. The goal of this study is to look at how the inquiry model is used to teach Indonesian subjects in elementary school, especially in Kelas 4. Also, one goal is for teachers to be able to do their job as learning facilitators as well as possible. Other goals are for students to learn how to use the scientific process, to build their knowledge through inquiry activities, for learning to be more student-centred (called "student-centred learning"), and for learning to be more meaningful so that it affects learning outcomes that go up. Can be used for the inquiry learning model, which trains students to think critically and produces many new scientific findings for students in each learning process.